Managing Face: A Pragmatic Analysis of Political Interview Discourse in Indonesia - Yafi, Mohammad Ali; Maris, Dewi (Journal of Pragmatics Research, 2025)
This study aims to analyze the facework strategies used by Indonesian political actors in public interviews to maintain their self-image and mitigate accountability in front of the public. Using a pragmatic approach with Brown and Levinson's (1987) politeness theory framework and Goffman's (1967) face theory, this study analyzed transcripts of the political talk show Mata Najwa, September 2023 edition, featuring Anies Baswedan (ABW) and Muhaimin Iskandar (MI). The analysis results showed that the three main strategies, positive politeness, negative politeness, and off-record politeness, were used selectively and contextually in responding to sensitive, confrontational, or ideological questions. Positive politeness was widely used to build solidarity and shared values, negative politeness to show caution and avoid direct responsibility, and off-record politeness to convey messages implicitly through metaphors, humor, and religious symbolism. Theoretically, these findings expand the development of politeness theory by incorporating dimensions of religiosity, hierarchy, and collective orientation that are unique to the political context of Southeast Asia. Empirically, this study shows that facework strategies function not only as linguistic tools but also as means of ideological and cultural framing in the Indonesian public discourse space.